The roles of SPBC409.08 and SPAC9.02c hypothetical genes in cell cycle and stress response, in Schizosaccharomyces pombe - Güngör, I; í–rs Gevrekci, A (Cellular and Molecular Biology, 2016)
Polyamine molecules are known to have important roles in the cell cycle control and fighting against stress in the cell. The mechanism and modification of polyamines are regulated by the cooperation of many proteins such as polyamine transporter proteins and polyamine acetyltransferases. In this study, our aim is to characterize two hypothetical Schizosaccharomyces pombe genes, SPBC409.08 and SPAC9.02c, which show sequence similarity to spermine family transporters and polyamine N-acetyltransferases, respectively. To this end, we generated deletion mutants of SPBC409.08 and SPAC9.02c genes using Bahler method and checked the cell cycle progression and stress responses of these mutants. Our results showed that SPBC409.08Î” cells showed some defects in the cell size, while SPAC9.02cÎ” cells showed some sensitivity to UV irradiation. These data support their potential roles in the cell cycle and stress response. To our knowledge our results are the first experimental characterization of these genes.